COUNTER RACIAL PREJUDICE REFLECTED IN FREEDOM WRITERS MOVIE - Rahmawati, Dessya Diah (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2022)
This study analyzes the anti-racism in the film Freedom Writers, directed and written by Richard LaGravenese. This study aims to identify anti-racism depicted in the film, describe how anti-racism is reflected in the film, and explain why a character named Erin Gruwell supports anti-racism in the film. This research is a library research. The type of data in this study is text, including narration, dialogue, and monologue. Data collection is done by watching and understanding the film’s storyline which is the object of this research. Qualitative data analysis was applied in this study, carried out in three stages, namely data reduction, data presentation, and conclusion drawing. This study shows that there are two aspects of anti-racism depicted in the film, namely education aspect and togetherness. Second, the anti-racism reflected in the film is illustrated by learning about tolerance for differences. And finally, the reason Erin Gruwell supports anti-racism in her classroom is that she wants to inspire students to learn and have a good view of differences.